2012
DOI: 10.4236/ojbd.2012.24014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Sickle Cell Anaemia and Thalassaemia in Central India

Abstract: Haemoglobinopathies are group of diseases characterized by abnormalities both quantitative and qualitative in the synthesis of haemoglobin. Haemoglobinopathies consist of sickle cell anaemia (SCA), thalassaemia (β T ) and variant haemoglobins. In India, they are responsible for the largest number of genetic disorders and hence are of great public health hazardous. In India major concerned haemoglobinopathic disorders are sickle cell anaemia and β-thalassaemia. Of the several abnormal haemoglobin molecules, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…These hemoglobinopathies are a serious public health problem in central India, reflecting genetic heterogeneity of population with burden on available medical facilities. [2] Population-based screening programs for the detection of thalassemia and sickle cell anemia are implemented in this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These hemoglobinopathies are a serious public health problem in central India, reflecting genetic heterogeneity of population with burden on available medical facilities. [2] Population-based screening programs for the detection of thalassemia and sickle cell anemia are implemented in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, the prevalence of sickle cell trait was found to be 3.4%. Urade [2] reported the prevalence of sickle cell trait to be 5.6%. Bhukhanvala et al [12] found its prevalence to be 2.41%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It affects worldwide more than 50 million people. Each year about 300,000 children are born with pathological hemoglobin of which 70% are affected by SCD [2]. Most of them die before the age of five years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also reported maximum report of cases of sickle cell disorder in mahar caste (11.08%) by Bhaskar et al and Ambekar S.S. et al reported maximum cases of beta thalassaemia amongst Navbuddhas. 8,9 In the present study splenomegaly was found most common in the patients of β-thalassemia major (83.33%) followed by sickle-Beta thalassemia (15 cases), sickle cell Anemia (2) and sickle cell trait (4).…”
Section: Discussionmentioning
confidence: 88%